Perception analysis of social networks’ privacy policy: Instagram as a case study - Talib, Shuhaili; Abdul Razak, Siti Munirah; Olowolayemo, Akeem Koye; Salependi, Melasari; Ahmad, Nur Fatihah; Kunhamoo, Syakila; Bani, Siti Khalijah (Institute of Electrical and Electronics Engineers Inc., 2014)
Social network emergence has had a remarkable impact on how people communicate and share information. It has increased revenues tremendously. However, it has added another problem to data confidentiality. This is due to the advances in communication technology that keep on producing a better, easier and cheaper way to communicate. However, the vulnerability somehow depends on the user itself, whether they care about their information. This paper examines users’ perceptions towards the existence of privacy policy in social networks. The research is intended to evaluate the extent of privacy policy awareness among users and the reason for low level of awareness. It also sought to evaluate other modes of communicating privacy policy that can be implemented for better user engagement.